1999
DOI: 10.1038/43922
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The development of cell or gene therapies for diseases involving cells that are widely distributed throughout the body has been severely hampered by the inability to achieve the disseminated delivery of cells or genes to the affected tissues or organ. Here we report the results of bone marrow transplantation studies in the mdx mouse, an animal model of Duchenne's muscular dystrophy, which indicate that the intravenous injection of either normal haematopoietic stem cells or a novel population of muscle-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Several studies have indicated that bone marrow (BM)-derived cells have the capacity to differentiate into various cell types through a process termed transdifferentiation [26][27][28][29][30][31][32][33]. However, these data are controversial, because several other studies reported that these cells fail to show such transdifferentiation [34][35][36][37][38][39].…”
Section: Role Of Featured Vascular Structure On Increased Islet Mass mentioning
confidence: 75%
“…Several studies have indicated that bone marrow (BM)-derived cells have the capacity to differentiate into various cell types through a process termed transdifferentiation [26][27][28][29][30][31][32][33]. However, these data are controversial, because several other studies reported that these cells fail to show such transdifferentiation [34][35][36][37][38][39].…”
Section: Role Of Featured Vascular Structure On Increased Islet Mass mentioning
confidence: 75%
“…Thus, the contribution of BMDC to diverse tissues has been described under normal and In recent years, it has been shown that bone marrowderived cells (BMDC) owe their plasticity to changes in pathological conditions. The contribution rate was always very scarce (2,42), but this low "basal" frequency, their fate, which allows their contribution to different cell populations in diverse organs (7,19,22,26,40,41,48), described under physiological conditions, was significantly increased when the target organs underwent inincluding the central nervous system (CNS) (2, 8,9,34,54). This surprising capacity has been considered a pojury (2,27,34,56), especially when accompanied by inflammation (23,38).…”
Section: Introductionmentioning
confidence: 99%
“…This method, which relies on the differential ability of stem cells to efflux the Hoechst dye, defines a rare population of stem cells that can adopt alternative fates in permissive environments (19,20). For example, these adult stem cells (identified using FACS and based on their ability to efflux Hoechst 33342 dye) have been shown to repopulate mutant (i.e., mdx or dystrophin deficient skeletal muscle) or injured adult skeletal muscle (19). Studies undertaken in the Sorrentino laboratory (St. Jude Children's Research Hospital, Memphis, TN) and our laboratory (UT Southwestern Dallas, TX) have established that the ability of adult stem cells to efflux Hoechst 33342 dye is dependent on the expression of Abcg2, which is a member of the family of ATP binding cassette (ABC) transporters (21,22).…”
Section: Somatic Stem Cell Populations In Adult Skeletal Musclementioning
confidence: 99%
“…This SP cell population is identified using Hoechst 33342 dye and dual wavelength flow cytometry as these cells are able to efflux the Hoechst dye (17,18). This method, which relies on the differential ability of stem cells to efflux the Hoechst dye, defines a rare population of stem cells that can adopt alternative fates in permissive environments (19,20). For example, these adult stem cells (identified using FACS and based on their ability to efflux Hoechst 33342 dye) have been shown to repopulate mutant (i.e., mdx or dystrophin deficient skeletal muscle) or injured adult skeletal muscle (19).…”
Section: Somatic Stem Cell Populations In Adult Skeletal Musclementioning
confidence: 99%